2020
DOI: 10.1016/j.jpsychores.2020.110256
|View full text |Cite
|
Sign up to set email alerts
|

Depression prevalence using the HADS-D compared to SCID major depression classification: An individual participant data meta-analysis

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…Rather, thresholds on these measures are typically set to cast a wide net for screening, and proportions of people above thresholds dramatically overestimate prevalence compared to validated methods based on diagnostic interviews. 610 In normal times, proportions of people above thresholds vary dramatically, even when the same measure and threshold are used. For example, the proportion of participants with scores of 10 or higher on the Patient Health Questionnaire-9 (PHQ-9), 11 a commonly used depression symptom measure, in large, randomly selected, regional or national general population samples pre-COVID-19, has been reported as 4% in Hong Kong (N = 6,028); 12 6% in Germany (N = 5,018); 13 7% in Shanghai, China (N = 1,045); 14 8% in the United States (N = 10,257); 15 8% in Alberta, Canada (N = 3,304); 16 11% in Sweden (N = 3,001); 17 and 22% in Jiangsu, China (N = 8,400).…”
mentioning
confidence: 99%
“…Rather, thresholds on these measures are typically set to cast a wide net for screening, and proportions of people above thresholds dramatically overestimate prevalence compared to validated methods based on diagnostic interviews. 610 In normal times, proportions of people above thresholds vary dramatically, even when the same measure and threshold are used. For example, the proportion of participants with scores of 10 or higher on the Patient Health Questionnaire-9 (PHQ-9), 11 a commonly used depression symptom measure, in large, randomly selected, regional or national general population samples pre-COVID-19, has been reported as 4% in Hong Kong (N = 6,028); 12 6% in Germany (N = 5,018); 13 7% in Shanghai, China (N = 1,045); 14 8% in the United States (N = 10,257); 15 8% in Alberta, Canada (N = 3,304); 16 11% in Sweden (N = 3,001); 17 and 22% in Jiangsu, China (N = 8,400).…”
mentioning
confidence: 99%
“…Ali et al (2016) conclude that the HADS-A is an adequate screener in LAMICs, but reported strong to very strong validity for primary studies that used the English (with Yoruba) version of HADS-A, and weak to strong validity for other language versions (Portuguese and Chinese) (Ali et al, 2016). Based on our meta-analyses and in line with Brehaut et al (2020), the evidence for the validity of the Arabic HADS is questionable.…”
Section: Discussionmentioning
confidence: 71%
“…In a recent IPDMA on the accuracy of the HADS-D to estimate depression prevalence, Brehaut et al . ( 2020 ) found the commonly used cut-off of 8 (‘doubtful cases’) significantly overestimated depression prevalence, while a cut-off of 11 (‘definite cases’) may either over- or underestimate depression prevalence. Ali et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three factors may feed this discrepancy. One is the publication of many crosssectional studies that report proportions above cut-offs on self-report measures, which are not designed for that purpose, [68][69][70][71][72] and assume that what are perceived as high numbers, generally, or sex differences, comparatively, must not have been present pre-COVID-19. 36 A second is the use of surveys that ask questions about well-being with COVID-19 explicitly assigned as a cause; illustrating the pitfalls of this, a study of over 2,000 young Swiss adult men found Mental Health Symptom Changes Following COVID-19 by Sex or Gender significant angst when questions were asked in this way, but no changes in validated measures of depression symptoms and stress from pre-COVID.…”
Section: Discussionmentioning
confidence: 99%